2006
DOI: 10.1002/fld.1172
|View full text |Cite
|
Sign up to set email alerts
|

A particle finite element method applied to long wave run-up

Abstract: SUMMARYThis paper presents a Lagrangian-Eulerian ÿnite element formulation for solving uid dynamics problems with moving boundaries and employs the method to long wave run-up. The method is based on a set of Lagrangian particles which serve as moving nodes for the ÿnite element mesh. Nodes at the moving shoreline are identiÿed by the alpha shape concept which utilizes the distance from neighbouring nodes in di erent directions. An e cient triangulation technique is then used for the mesh generation at each tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…We found that the mass increased about 0.2% when the circular drop impacted the water. Afterwards, the mass became small, which was very similar to the results in [21] and the error was about −2.5% at time 4 s. Figure 11 illustrates the error of the mass when the mesh-push method was used. First, the order of magnitude was about 10 −5 most of the time but there were some special points with large negative errors.…”
Section: The Mass/volume Conservationsupporting
confidence: 73%
See 3 more Smart Citations
“…We found that the mass increased about 0.2% when the circular drop impacted the water. Afterwards, the mass became small, which was very similar to the results in [21] and the error was about −2.5% at time 4 s. Figure 11 illustrates the error of the mass when the mesh-push method was used. First, the order of magnitude was about 10 −5 most of the time but there were some special points with large negative errors.…”
Section: The Mass/volume Conservationsupporting
confidence: 73%
“…As illustrated in Figure 5(a), assume that all the angles after deformation are larger than half of their initial values, respectively. Take 1 as an example; its original value is 1 = atan2(|r 21 ×r 31 |, r 21 ·r 31 ), and the angle after deformation is set to 1 = 1 2 . An equation like Equation (19) can be derived and solved to get a suitable time step.…”
Section: The Adaptive Time Stepmentioning
confidence: 99%
See 2 more Smart Citations
“…The rapid distortion of used mesh, and thus the frequent re-meshing, represents the biggest challenge to overcome for scientists. The paper by Birknes and Pedersen [33] could be taken as a typical work. It introduces the use of the 'particle FEM (PFEM)' to the SWE to simulate the long wave run-up.…”
Section: The Shallow Water Equations (Swe)mentioning
confidence: 99%